2023
DOI: 10.1002/hlca.202300008
|View full text |Cite
|
Sign up to set email alerts
|

Halogen‐Bonded Liquid Crystals

Abstract: While the halogen bond has been recognised and studied for over a hundred years, it is only in more recent times that chemists have begun to apply it and see its possibilities as another supramolecular interaction that can be deployed in the preparation of materials. This review takes one of those areas, liquid crystals, and considers examples of motifs that have been deployed successfully to generate new mesogens. In particular, rather than attempting to be comprehensive, the article reviews critically data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 78 publications
(123 reference statements)
0
12
0
Order By: Relevance
“…[10][11][12][13] Analogous work has also been carried out in the field of halogen bonding. 14,15 In both hydrogen-and halogen-bonded liquid crystals, one area of discussion has been the extent to which it can be shown (or not) that the clearing point (the temperature at which the liquid crystallinity is lost and an isotropic liquid is formed) is driven either by the natural clearing of the new supramolecular complex or by the rupture of the supramolecular linkage (hydrogen or halogen bond) to form non-mesomorphic components. Aspects of this have recently been reviewed where it was concluded that at least for halogen-bonded complexes, both possibilities likely exist, whereas for hydrogen-bonded mesogens, there is good experimental evidence that the hydrogen bond is preserved through clearing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12][13] Analogous work has also been carried out in the field of halogen bonding. 14,15 In both hydrogen-and halogen-bonded liquid crystals, one area of discussion has been the extent to which it can be shown (or not) that the clearing point (the temperature at which the liquid crystallinity is lost and an isotropic liquid is formed) is driven either by the natural clearing of the new supramolecular complex or by the rupture of the supramolecular linkage (hydrogen or halogen bond) to form non-mesomorphic components. Aspects of this have recently been reviewed where it was concluded that at least for halogen-bonded complexes, both possibilities likely exist, whereas for hydrogen-bonded mesogens, there is good experimental evidence that the hydrogen bond is preserved through clearing.…”
Section: Introductionmentioning
confidence: 99%
“…Aspects of this have recently been reviewed where it was concluded that at least for halogen-bonded complexes, both possibilities likely exist, whereas for hydrogen-bonded mesogens, there is good experimental evidence that the hydrogen bond is preserved through clearing. 15 One of the factors that may be at play in thinking about whether a complex may rupture on heating is the strength of the halogen or hydrogen bond. In the former case, this will depend upon the degree of electrophilicity of the iodine 16 (halogen-bonded liquid crystals are almost invariably formed using electron-poor iodines and the basicity of the (invariably) pyridine donor appears to have little effect 17 ), while in the latter case it will relate to the acidity of the hydrogen donorin this case a phenol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of functional liquid‐crystalline (LC) materials have been developed by designing LC molecules and composites [6–10] . In the design of functional LC materials, chemical modification of functional molecules with mesogenic units is a general approach [11–15] . Supramolecular interactions have also been used to obtain functional liquid crystals [11–15] .…”
Section: Introductionmentioning
confidence: 99%
“…In the design of functional LC materials, chemical modification of functional molecules with mesogenic units is a general approach [11–15] . Supramolecular interactions have also been used to obtain functional liquid crystals [11–15] . Moreover, use of multiple mesogenic units allows the incorporation of complex functional molecules, inorganic nanoclusters, and metal nanoparticles into the LC states [16–25] .…”
Section: Introductionmentioning
confidence: 99%